The role of product information on consumer sensory evaluation, expectations, experiences and emotions of cricket-flour-containing buns - Pambo, K.O.; Okello, J.J.; Mbeche, R.M.; Kinyuru, J.N.; Alemu, M.H. (Elsevier, 2018)
Studies suggest that consumer' acceptance of edible insects can be enhanced by processing and blending them with familiar food products. This is however, expected to result in changes in some sensory attributes. In this study, we investigated how consumers evaluate the appropriateness of sensory attributes of a common bakery product (buns) that was blended with cricket-flour i.e., cricket-flour-containing (CFC) buns. We also tested whether provision of information can modulate the sensory evaluations, personal involvement and emotions. The study is based on a field experiment involving 432 participants drawn from rural communities in Kenya. Participants were randomly assigned to 3 information treatment groups: i) Control group - received only general information, ii) Treatment 1 – received general information and information about the benefits (i.e., positive attributes), iii) Treatment 2 – received general information and information about the potential drawbacks (i.e., negative attributes). Participants evaluated the CFC buns before and after tasting using Just-About-Right (JAR) scale. Results indicate that providing product information affected sensory evaluation of the product's sensory attributes. They also indicate that actual tasting of the CFC buns improved the convergence of sensory evaluation of the attributes towards the ideal level. Results further show that CFC buns elicited more positive feelings with little differences in the emotional profiles between the information treatments, which suggests general interest in the buns. These results provide useful insights on how to enhance consumer acceptance of insect-based foods. We discuss the implications of the findings.